Acute effects of whole-body vibration with resistance exercise on postexercise blood pressure and oxygen consumption in prehypertensive adults - Zachary S. Zeigler; Pamela Diane Swan (Elsevier, 2016)
Background/Objective: Research on the acute health effects of whole-body vibration with resistance exercise (WBV + RE) for clinical populations is limited. This randomized crossover trial evaluated postexercise hypotension and excess postexercise oxygen consumption (EPOC) in response to three conditions: WBV + RE, RE alone, and control (CON) in 11 prehypertensive (systolic/diastolic blood pressure: 120-139/80-89 mmHg) adults. Methods: Following a 12-hour fast with no exercise for the previous 24 hours, resting VO2 and blood pressure (BP) were measured. WBV + RE was performed while standing barefoot on a vibration platform (Pneumex Pro-Vibe) and lifting a bar of 10% body weight. Fifteen repetitions of nine exercises were performed using a 1-minute-to-30-second exercise:rest ratio. RE was identical to WBV + RE but without vibration. During CON, participants remained seated for 15 minutes. Following exercise, VO2 was measured continuously and BP every 15 minutes for 3 hours. Results: Postexercise hypotension and EPOC were significantly different for WBV + RE compared with RE and CON (p <0.001). Postexercise systolic BP was significantly lower for WBV + RE as compared with RE or CON, while diastolic BP was lower for both WBV + RE and RE compared with CON (p < 0.001; WBV + RE: 124 ± 2/72 ± 6 mmHg; RE: 126 ± 2/71 ± 6 mmHg; CON: 128 ± 2/73 ± 6 mmHg). EPOC was significantly (p < 0.001) higher at 15 minutes postexercise for WBV + RE as compared with RE. Conclusion: Compared with RE alone, a single bout of WBV + RE resulted in a greater postexercise hypotension response and higher EPOC.